ASCOT: Autologous Bone Marrow Stem Cell Use for Osteoarthritis of the Thumb—First Carpometacarpal Joint. Issue 9 (September 2017) - Murphy, Matthew P.; Buckley, Christina; Sugrue, Conor; Carr, Emma; O'Reilly, Aine; O'Neill, Shane; Carroll, Sean M.
Abstract : Background: The first carpometacarpal joint (CMCJ) in the hand is a commonly affected joint by osteoarthritis. It causes significant thumb base pain, limiting functional capacity. Microfracturing and application of autologous stem cells has been performed on large joints such as the knee but has never been evaluated for use in the smaller joints in the hand. Our aim was to determine the potential benefit of microfracturing and autologous bone marrow stem cells for treatment of osteoarthritis of the first CMCJ in the hand. Methods: All inclusion criteria were satisfied. Preoperative assessment by the surgeon, physiotherapist, and occupational therapist was performed. The first CMCJ was microfractured and the Bone Marrow Stem Cells were applied directly. Postoperatively, the patients were followed up for 1 year. Results: Fifteen patients met inclusion criteria; however, 2 patients were excluded due to postoperative cellulitis and diagnosis of De Quervain's tenosynovitis. The mean scores of the 13-patient preoperative and 1 year follow-up assessments are visual analog score at rest of 3.23–1.69 ( P = 0.0292), visual analog score on activity of 7.92–4.23 ( P = 0.0019), range of motion 45.77o–55.15o ( P = 0.0195), thumb opposition score 7.62–9.23 ( P = 0.0154), Disability of the Arm, Shoulder and Hand score of 51.67–23.08 ( P = 0.0065). Strength improved insignificantly from 4.7 kg preoperatively to 5.53 kg at 12 months ( P = 0.1257). All patients had a positive Grind test preoperatively and a negative test after 12 months. Conclusions: This innovative pilot study is a new approach to osteoarthritis of the thumb.